Análisis comparativo de la estructura de los Programas Televisivos Matinales en el Ecuador - Bueno Almeida, Irene Eloísa (2021)
The morning television programs contain novel and interesting topics for which they stand out, these programs are aimed at housewives and among the most prominent in Ecuador we find in Contact, from Casa En Casa, Morning News that stand out for their trajectory. At present, morning shows have changed their content a bit and this research aims to carry out a comparative analysis of the structure of morning television programs in Ecuador and to be able to determine the influence they exert on their audience. The methods used in data collection were to search for information on the subject, and the observation sheet, it should be emphasized that the following research will serve future research on morning programs and thus have different perspectives on this study.